Embleminės iliustracijos Jonušui Radvilai (1612-1655) dedikuotuose leidiniuose - Paliušytė, Aistė (Knygotyra, 1998)
Jonušas Radvila, the hetman of the Lithuanian Grand Duchy and the voivode of Vilnius, was one of the most ambitious art as well as book patrons of the first half of the seventeenth century in the LGP. A large part of his ordered editions were occasional panegyrics. They were decorated by emblematic illustrations, which were very popular and used in books of the first half of the seventeenth century in the LGP. Heraldic emblems, glorifying the patron of the book according to the motifs of his coat of arms, were frequently used in the books ordered by Jonušas Radvila. These emblems were genetically connected with medieval devices and expressed the representative aims of a noble. The heraldic engravings were first used in the dedications for Jonušas Radvila in the panegyrics: Krysztalz popiolu by W. Cieciszewski (Vilnius, 1643) and Tyara wiecznosci by A. Witkowski (Vilnius, 1643), issued on the occasion of his wife Kotryna Potocka’s funeral. Emblematic engravings also decorated Mausolaeum na akt pogrzebowy by K. J. Woysznarowicz (Vilnius, 1643) and Parentalis Splendor by the same author (Vilnius, 1647?). Salutatio by V. Thilo (Karaliaučius, 1651)—an edition issued on the occasion of the victory of the hetman against the Cossacks—was also decorated by emblematic engravings. The dedication of S. Jaugelis Telega in Kniga nobažnistės krikščioniškos (Kėdainiai, 1653) was begun by a magnificent heraldic engraving. The motives of emblematic engravings, their origin, as well as their relation to the text interpreting the picture, are analyzed in the article. The quality of the engravings was very uneven. The greatest attention was paid to the traditionalism of the motifs, the recognition of the signs, and the clarity of the meaning. It often deviated from the trinomial structure characteristic of Western academic literary emblems. The rhymed part of an emblem, which explains and interprets a picture, was often extended. At the same time, the meanings of the emblematic images were enriched, and the simple motifs of the engravings became more rhetorical. The emblematic engravings enhanced the representative character of the editions ordered by Jonušas Radvila. They decorated the book and allegorically conveyed the ideas of the origin, rank, morals, and glory of a noble. The engravings, placed at the beginning of the dedication or repeated throughout the book, made the manifestation of the patron more visible and intensified the panegyric suggestion.